Sweden, a Society of Covert Racism: Equal from the Outside : Everyday Racism and Ethnic Discrimination in Swedish Society - Schömer, Eva (Oñati Socio-Legal Series, 2016)
Sweden is widely considered to have one of the most equal and gender-equal societies in the world. But the Swedish society is also one in which the Labour Court can find discrimination when a 60-year-old ‘Swedish’ ‘white’ woman fails to get a job interview - yet not when workers call a colleague of Gambian background ‘blackie’, ‘big black bastard’, ‘the African’, and ‘svartskalle’, or a man of Nigerian background ‘Tony Mogadishu’ and ‘Koko stupid’. In this article, I will try to explain the logic behind these positions. I will also suggest an extended jurisprudential methodology that might help to prevent laws and the legal system from reinforcing societal processes of racialization. In this article I will argue that it is necessary to develop the legal methods to make it possible to forestall and prevent racism. To prevent everyday racism in the way intended by the law in books, the courts must take into account the living law and the law in action. If the courts are allowed to continue applying the law according to their whim, without even considering their position as representatives for the power of dominant ‘white’ groups over subordinated people of colour, then it is obvious that the living law that is the dominant discourse of ‘white’ normalcy will never change.